Analysis of Differences in the Approach of BK Teachers (BK and Non BK Education Graduates) in Overcoming Student Discipline Problems - Andi Tenri Aulia Martiandi; Sandi Pratama; Alamsyah (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Student discipline problems are a common challenge often faced by Guidance and Counselling (G&C) teachers in schools. Differences in educational background raise questions about the effectiveness and approaches used by BK teachers, who are graduates of BK Education and non-BK institutions, in dealing with student discipline problems. Using a mixed-method approach that combines quantitative and qualitative methods, this study collected data through questionnaires, in-depth interviews, and observations of 42 students and BK teachers. The results showed significant differences in the approaches used by BK teachers who were graduates of BK Education and those who were not, particularly in dealing with student discipline problems. BK teachers who were graduates of BK Education tended to be more systematic, empathetic, and grounded in counselling theory. In contrast, non-BK teachers employed more authoritative approaches and drew on personal experiences. In conclusion, there were significant differences in the approaches used by BK teachers who were graduates of BK Education and non-BK in dealing with student discipline problems, where BK graduates tended to apply more professional strategies based on guidance theory. The implication of this study is the need to improve the competence of non-BK BK teachers through more in-depth training and certification in the field of guidance and counselling. In addition, schools need to develop policies that encourage synergy between educational approaches and disciplinary approaches, creating a more conducive school environment for the development of student character.